Improving Student Social Interaction Ability Using Problem Based Learning (PBL) Method in The Subject Of Aqidah Morals at Min 10 Boyolali Academic Year 2022/2023 - Khoirudin; Joko Subando; Meti Fatimah (Risâlah Jurnal Pendidikan dan Studi Islam, 2024)
This study aims to determine the Problem Basic Learning (PBL) method in the Aqeedah Akhlak subject can improve social interaction abilities of students at MIN 10 Boyolali in the 2022/2023 academic year. This research is a type of classroom action research. This research was conducted from April to June 2023. The subjects of this study were Class IV students at MI N 10 Boyolali with a population of 53 students, so all were taken. Data is taken through documents and questionnaire scores, with the T-Test test. The PBL method can improve students' social interaction skills by 49.8% starting from the pre-action, then continuing in cycle I to increase to 68.8% and in cycle II to increase again to 78.4%. The use of the PBL method is applied to students of class IV MIN 10 Boyolali in the Aqidah Akhlak subject so that students can more easily and quickly improve their social interaction skills.